The Nutrition Support Team - Duna Penn (Indonesian Pediatric Society, 1997)
The development of nutrition support teams in the United States was stimulated in the 1970's and 80’s by reports concerning the prevalence and consequences of malnutrition among hospitalized patients. Butterworth's provocative paper,